Nexus between aging and health expenditure: An evidence from Nepal (Journal of Innovation in Academia, 2025)
This study investigates the causal relationship between aging and healthcare expenditure in Nepal. To examine this causal connection, we employed a parsimonious VAR-based Wald test, Granger causality analysis, impulse response functions (IRFs), and forecast error variance decompositions using time series data from 2000 to 2020. The findings of the analysis reveal a substantial positive correlation between the proportion of elderly people and healthcare expenditure, indicating that as the population ages, healthcare costs and the demand for healthcare services tend to rise. The IRF analysis further confirmed that an innovation or shock in the aging index (AI) led to a subsequent increase in per capita health expenditure (HPC). Granger causality also reveals a unidirectional causal linkage from the aging index to per capita health expenditure. In addition, the study highlights the positive impact of aging on life expectancy in Nepal.